2016
DOI: 10.1093/europace/euw321
|View full text |Cite
|
Sign up to set email alerts
|

Patients upgraded to cardiac resynchronization therapy due to pacing-induced cardiomyopathy are at low risk of life-threatening ventricular arrhythmias: a long-term cause-of-death analysis

Abstract: Aims: Upgrade to cardiac resynchronization therapy (CRT) should be offered to patients who have developed pacing-induced cardiomyopathy with conventional right ventricular pacing. The extent to which those patients would also benefit from defibrillator back-up at the time of CRT upgrade is, however, unknown. Methods:Retrospective observational cohort study of 199 patients with pacing-induced cardiomyopathy (without history of sustained ventricular arrhythmia), including 104 upgraded to CRT-Pacemaker (CRT-P) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…Over a mean follow‐up of 5.5 years, three of 104 (2.9%) patients in the CRT‐P arm had a primary arrhythmic death (6.2 sudden arrhythmic deaths per 1,000 patient‐years). The authors concluded that patients with pacing‐induced cardiomyopathy and no prior ventricular arrhythmias who are upgraded to CRT may not derive any significant benefit from the addition of a defibrillator . In contrast, we found that CRT‐D upgrade was consistently superior to CRT‐P upgrades with respect to the three main endpoints, even after inverse probability weighting.…”
Section: Discussioncontrasting
confidence: 58%
“…Over a mean follow‐up of 5.5 years, three of 104 (2.9%) patients in the CRT‐P arm had a primary arrhythmic death (6.2 sudden arrhythmic deaths per 1,000 patient‐years). The authors concluded that patients with pacing‐induced cardiomyopathy and no prior ventricular arrhythmias who are upgraded to CRT may not derive any significant benefit from the addition of a defibrillator . In contrast, we found that CRT‐D upgrade was consistently superior to CRT‐P upgrades with respect to the three main endpoints, even after inverse probability weighting.…”
Section: Discussioncontrasting
confidence: 58%
“…The narrowing of QRS complexes, as well as the resolution of electromechanical dyssynchrony, for example, apical rocking and septal flash in echocardiography after CRT, is a well‐described predictor of reverse LV remodeling, LVEF improvement, and a reduction in the number of ventricular arrhythmia episodes and mortality 11,16,21,24 . Correction of severe dyssynchrony seems to be crucial in the PICM population in the absence of a history of ventricular arrhythmias influencing survival despite the use of HV therapy 2,7,8,9 . Our findings, by directly comparing the PM/CRT‐P versus the PM/CRT‐D group, seems to confirm these observations in the patients at high risk of PICM, without severe, irreversible LV dysfunction.…”
Section: Discussionmentioning
confidence: 76%
“…The current European Society of Cardiology guidelines give II B recommendations for an upgrade from right ventricular to biventricular (BiV) pacing in patients who develop worsening Heart Failure (HF) due to a high percentage of RVP, despite Optimal Medical Therapy (OMT) 6 . However, there are only a few data on whether the addition of implantable cardioverter defibrillator (ICD) to CRT in the PICM population affects survival 7,8,9 …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of PICM ranges from 12% to 20%, and the risk factors for PICM include frequent RV pacing, QRS duration, preexisting left bundle branch block, and LV systolic dysfunction prior to pacemaker implantation [1], [2], [4], [5]. Biventricular pacing is effective for preventing and reversing PICM, and is endorsed by the practice guidelines for selected cases [1], [2], [3], [4], [6].…”
Section: Introductionmentioning
confidence: 99%